1976
DOI: 10.1070/qe1976v006n03abeh011013
|View full text |Cite
|
Sign up to set email alerts
|

Electric-discharge laser initiated in the active medium

Abstract: The paper is almost entirely mathematical, and calculates the effect on the visibility of an object, illuminated by a projector, of the scattering and absorption of the light by the atmosphere. The discussion is divided into three parts dealing separately with the light reflected from the object from the incident beam, with the brightness of the atmospheric background due to scattered light, and of the conditions of visibility as functions of the two previous quantities. Numerical solutions of the equations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The number of new channels increases with time, they disperse from the middle to the periphery of the gap, and their brightness gradually achieves that of the first Fig. 18 Schemes of experimental setups for studying the SIVD dynamics: (7) ignitor and (2) monitoring conductors. Apollonov: High-power self-controlled volume-discharge-based .…”
Section: Fig 12mentioning
confidence: 98%
“…The number of new channels increases with time, they disperse from the middle to the periphery of the gap, and their brightness gradually achieves that of the first Fig. 18 Schemes of experimental setups for studying the SIVD dynamics: (7) ignitor and (2) monitoring conductors. Apollonov: High-power self-controlled volume-discharge-based .…”
Section: Fig 12mentioning
confidence: 98%
“…Therefore, runaway electron beams registered in gas diodes have not found practical application. On the other hand, in [10][11][12][13][14][15] it was demonstrated that large dozes of soft x-ray radiation could be obtained in a nonuniform electric field in discharges in working mixes of CO 2 , exciplex lasers, and in air. The maximum energy of x-ray radiation was in the region of 5-20 keV, and the expose doze in the active volume was as great as 60-300 R [14].…”
Section: Introductionmentioning
confidence: 99%
“…3) For pulse edge duration of a few nanoseconds, only soft x-ray radiation with a maximum at energies of 5-10 keV is registered under gap breakdown conditions [10][11][12][13][14][15]. Moreover, the main source of soft x-ray radiation is the discharge plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, preliminary ionization of a discharge gap by different sources of ionizing radiation [2] or decreasing pressure in a gas gap [3] are used to form a high-pressure volume pulse discharge. A pulse discharge in a non-uniform electric field is used for preionization of the main discharge in pulsed electrodischarge lasers (exciplex, CO2 and others [4,5]). The specific energy input in a volume discharge maybe essentially increased up to 100 MW/cm3 at nanosecond duration of a voltage pulse with a steep leading edge (unities -fractions of a nanosecond) [6,7].…”
Section: Introductionmentioning
confidence: 99%